The Practice of Electroconvulsive Therapy in Children and Adolescents in the Czech Republic - Hořínková, Jana; Bartečků, Elis; Kališová, Lucie (The journal of ECT, 2021)
OBJECTIVES: The aim of this study was to describe the practice of electroconvulsive therapy (ECT) in child and adolescent patients in the Czech Republic. METHODS: We conducted a mail questionnaire survey among Czech facilities associated with the Association of Child and Adolescent Psychiatry, and university hospitals with inpatient psychiatric wards, focused on the practice of ECT between 2013 and 2017 in patients younger than 18 years. RESULTS: Of 18 approached facilities, 13 had access to ECT, and only 6 used ECT on 16 patients. The most common diagnosis was schizophrenia or related disorders (68.75% of patients), and the most common reason for ECT was catatonic symptoms (37.5%). The most common ECT methodology was bitemporal electrode placement with brief-pulse current (62.5%). In 2 patients, ECT was terminated because of ineffectiveness and in 1 patient because of adverse reaction. In other patients, ECT ended after achieving a clinical effect. The most common adverse effect was transient memory impairment in a quarter of the patients. The number of pharmacological treatment attempts before ECT significantly correlated with hospitalization length. CONCLUSIONS: The utilization of ECT among children and adolescents was low. It was usually used in severe conditions after several pharmacological treatment attempts, which may indicate reluctance among providers to use this modality. A number of pharmacological attempts were associated with longer hospitalizations. In the majority of patients, ECT was effective and safe. On the other hand, the monitoring of cognitive adverse effects was insufficient and could be improved.
Keywords: schizofrenie; Czech Republic; lidé; mladiství; Adolescent; Electroconvulsive Therapy; Schizophrenia; Treatment Outcome; výsledek terapie; dítě; Child; Catatonia; Humans; psychiatrické oddělení nemocnice; katatonie; elektrokonvulzívní terapie; Česká republika; Psychiatric Department, Hospital